2003
DOI: 10.1523/jneurosci.23-26-08955.2003
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure and Biochemical Mechanisms Underlying Nigrostriatal Inclusions and Cell Death after Proteasome Inhibition

Abstract: Mutation of genes encoding for various components of a metabolic pathway named the ubiquitin-proteasome system (UP) leads to inherited forms of Parkinson's disease (PD), whereas various components of the UP are constantly present within neuronal inclusions, Lewy bodies, that characterize most genetic and sporadic forms of PD. It has been hypothesized that impairment of this metabolic pathway might be a common mechanism for the onset of PD, and a recent study demonstrated a dysfunction of the UP system within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
142
2
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(157 citation statements)
references
References 47 publications
12
142
2
1
Order By: Relevance
“…The percentage of apoptotic cells reaches 16% at a dose of 1µM and 23% at a dose of 5µM, which is similar to that of undifferentiated PC12 cells 11 and primary rat midbrain dopaminergic neurons 22 respectively. Although it is not a direct comparison, it may suggest at least that cholinergic cells are vulnerable to the proteasomal inhibition.…”
Section: Figure 2: Effect Of Lact On Mitochondrial Membrane Potentialsupporting
confidence: 61%
See 1 more Smart Citation
“…The percentage of apoptotic cells reaches 16% at a dose of 1µM and 23% at a dose of 5µM, which is similar to that of undifferentiated PC12 cells 11 and primary rat midbrain dopaminergic neurons 22 respectively. Although it is not a direct comparison, it may suggest at least that cholinergic cells are vulnerable to the proteasomal inhibition.…”
Section: Figure 2: Effect Of Lact On Mitochondrial Membrane Potentialsupporting
confidence: 61%
“…All of these have triggered big interest in exploring the role of UP dysfunction in the pathogenesis of PD. Recently several studies have revealed that proteasome inhibitors could produce excellent PD animal models [11][12][13] , ABSTRACT: Objective: Ubiquitin proteasome system dysfunction is believed to play an important role in the development of Parkinson's disease (PD), and almost all studies till now have mainly focused on the susceptibility of dopaminergic neurons to proteasome inhibition. However, in fact, there are many other types of neurons such as cholinergic ones involved in PD.…”
mentioning
confidence: 99%
“…Several lines of evidence suggest that UPS dysfunction may be involved in the pathogenesis of PD (Dawson and Dawson, 2003;Dauer and Przedborski, 2003;Fornai et al, 2003Fornai et al, , 2005Singleton et al, 2003;Sawada et al, 2004;Rideout et al, 2005). In particular, it appears that UPS dysfunction coupled with other stressors, such as oxidative stress and mitochondrial inhibition, is toxic to nigrostriatal dopamine neurons (Giasson et al, 2000;Hoglinger et al, 2003;Elkon et al, 2004;Betarbet et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of Lewy bodies suggests that the ubiquitin-proteasome system (UPS) does not adequately clear misfolded or damaged proteins, leading to protein aggregation and culminating in degeneration of SN dopamine neurons. Consistent with this idea, proteasome inhibitors have been reported to cause dopamine cell death in vitro (McNaught et al, 2002;Petrucelli et al, 2002), and intrastriatal infusion of proteasome inhibitors results in the presence of α-synuclein-positive inclusions and degeneration of SN dopamine neurons (Fornai et al, 2003;Miwa et al, 2005). McNaught et al (2004) reported that systemic administration of the proteasome inhibitor Zlle-Glu(OtBu)-Ala-Leu-al (PSI) causes the progressive degeneration of nigrostriatal dopamine neurons and ubiquitinated, α-synuclein-immunoreactive (-ir) intracytoplasmic inclusions in surviving dopamine neurons, thus mimicking the pathology of PD.…”
Section: Introductionmentioning
confidence: 86%
“…Impairment of the proteasomal system in Parkin KO mice and in PC12 cells leads to mitochondrial dysfunction (142,148), and mitochondrial dysfunction results in impairment of proteasomal function (149). Inhibition of the proteasomal system results in formation of ␣-SYN aggregates (12,78,79), and aggregates of ␣-SYN can impair proteasomal function (83).…”
Section: Conclusion Questions and Hypothesesmentioning
confidence: 99%